Fibrinolytic Response to lnterferon-a in Healthy Human Subjects - Corssmit, E P M; Levi, M; Hack, C E; ten Cate, J W; Sauerwein, H P; Romijn, J A (Thrombosis and Haemostasis, 1996)
Interferons (IFNs) are used for a variety of disorders. It has been postulated that part of the effects of IFN may be mediated by IFN-induced modulation of endothelial cells. Since the principal activating and inhibiting factors of the fibrinolytic system are synthesized and stored in endothelial cells, we have studied the effects on fibrinolysis and coagulation of the administration of recombinant IFN-α (5 × 106U/m2) to healthy human subjects (n = 8) in a randomized controlled cross-over study. IFN-α significantly increased plasma levels of tissue-type plasminogen activator (t-PA) and urokinase-type plasminogen activator (u-PA). Simultaneously, plasma levels of the inhibitor of plasminogen activation, PAI-1, sharply increased. The net effect on plasma plasminogen activator activity (PA-activity) was a modest increase to 116% of baseline, however without a significant effect on plasmin generation, as reflected by plasma levels of plasmin-α2-antiplasmin complexes. IFN-α had no effect on the plasma levels of thrombin-antithrombin III (TAT) complexes.We conclude that despite considerable effects on endothelial cells, IFN-α does not significantly alter the coagulant-fibrinolytic balance, although the occurrence of such changes under pathological circumstances is not excluded.